2022
DOI: 10.1038/s41598-022-12814-0
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater irrigation reduces overall poverty but increases socioeconomic vulnerability in a semiarid region of southern India

Abstract: The development of irrigation is generally considered an efficient way to reduce poverty in rural areas, although its impact on the inequality between farmers is more debated. In fact, assessing the impact of water management on different categories of farmers requires resituating it within the different dimensions of the local socio-technical context. We tested this hypothesis in a semi-arid area in Karnataka, South India, where groundwater irrigation was introduced five decades ago. Using the conceptual fram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 65 publications
(80 reference statements)
1
4
0
Order By: Relevance
“…The above findings were in accordance with the findings (9) who also reported that high cost of equipment, requirement of additional tank, non -availability spare parts, poor subsidy provision' , and 'high cost of liquid fertilizer' were the major constraints in adoption of drip irrigation technology. https://www.indjst.org/…”
Section: Financial Constraintssupporting
confidence: 91%
“…The above findings were in accordance with the findings (9) who also reported that high cost of equipment, requirement of additional tank, non -availability spare parts, poor subsidy provision' , and 'high cost of liquid fertilizer' were the major constraints in adoption of drip irrigation technology. https://www.indjst.org/…”
Section: Financial Constraintssupporting
confidence: 91%
“…This study contributes to the filling of the following research gaps. First, rich findings are attained for irrigation-related infrastructure (Adetoro et al ., 2022; Biru et al ., 2020; Fischer et al ., 2022). However, rural infrastructure includes a broader range of facilities such as roads, electricity and information and communication technology (ICT).…”
Section: Conceptual Framework and Literature Reviewmentioning
confidence: 99%
“…While the agrarian reforms introduced in the decades following India's independence undoubtedly allowed farmers and former tenants to formally own private property, and ended the taxation system that existed earlier, there was no large-scale distribution of land, and numerous families, mostly from lower castes, remained landless. Cultivated land is hence very unequally distributed among cultivators (Figure 2), alongside a large contingent of landless farming households accounting for about 40% of India's (Lucas, 2014;Tessier and Taghavi, 2019;Fischer et al, 2022) rural households (Rawal, 2008, based on NSS data). In the 2011 Census, for the first time, out of a total of 263 million farmers (including "marginal" workers), the number of agricultural laborers (144 million) surpassed the number of cultivators (119 million) (Dorin and Aubron, 2016: Figure 3).…”
Section: Land Inequality With High Labor Intensitymentioning
confidence: 99%